11C-Methionine Positron Emission Tomography in the Follow-up of Meningiomas After Stereotactic Radiotherapy. (16th November 2020) - Jeltema, Hanne-Rinck; Jansen, Marnix; Heesters, Mart; Glaudemans, Andor; van Dijk, Marc
Abstract: INTRODUCTION: 11C-Methionine positron emission tomography (MET-PET) is useful for target delineation in meningioma patients undergoing stereotactic radiotherapy (SRT). Radiologic follow-up of meningiomas at the skullbase or near vascular structures is difficult, especially after previous radiotherapy and/or neurosurgery. During follow-up, radiotherapy effects and postoperative scarring can mimic tumor progression. METHODS: A retrospective analysis of MET-PET results after SRT was performed in twelve meningioma patients. The SUVmax and SUVpeak were calculated for the tumor, the right frontal grey matter (cortex) and the healthy contralateral side (mirror). Tumor-to-normal (T/Ncortex and T/Nmirror) ratios were calculated. Tracer uptake ratios of patients with progressive and stable disease were compared using the Mann-Whitney U test. RESULTS: Median follow-up after SRT was 51.5 months (range 17–133). The mean T/Ncortex ratios for the SUVmax and SUVpeak were 2.89 (SD 0.70) and 2.63 (SD 0.79) respectively. The mean T/Nmirror ratios for the SUVmax and SUVpeak were 3.30 (SD 0.84) and 2.87 (SD 0.94). Three patients experienced disease progression after SRT. The mean T/Ncortex ratios of patients with progressive disease and with stable disease were 2.72 and 2.94 (p = 0.78) for SUVmax and 2.50 and 2.67 (p = 0.64) for SUVpeak. The mean T/Nmirror ratios of patients with progressive disease and with stable disease were 3.39 and 3.27 (p = 0.93) for SUVmax and 2.87 and 2.87 (p = 0.78) for SUVpeak. CONCLUSION: 11C-Methionine uptake remains remarkably high in meningiomas after SRT. There was no significant difference in SUV T/N ratio between patients with and without progressive disease. This suggests that addition of MET-PET to the regular follow-up of meningioma patients after SRT does not add extra information. Possibly other PET modalities (e.g. 68-Ga DOTATATE-PET) are more informative regarding disease activity in meningioma patients after SRT.